Some Evidence of Feasibility: Scenario-Based Programming. (Computer (00189162), 2008)
The article discusses scenario-based computer programming. This is a programming language that programmers can use interactively as a "play-in" approach to specifying reactivity and, in 1998, a collaboration involving Werner Damm created the language of live sequence charts (LSCs). LSCs is a temporal visual formalism that lengthens classical message sequence charts (MSCs) by being multimodal which allows existential and universal flavors, hot and cold, for the charts and internal elements. It is a language that enables a programmer to specify scenarios with what can, might, must, and cannot happen. Work on making LSCs better with Rami Marelly has resulted in "play-in" and "play-out" as well as the Play-Engine tool which supports both techniques.